A study on the factors influencing pet groomers' work related musculoskeletal discomfort in the shoulders, lower back and hands/wrists - Gosiaco, Katherine Grace T. (Animo Repository, 2012)
Background: Previous studies have not investigated musculoskeletal discomfort (MSDC) of pet groomers although they are exposed to several ergonomic risk factors such as awkward postures, forceful exertions, and repetitive motions. It is not known which of these risk factors significantly contribute to incidence of MSDC. An initial investigation through Nordic Musculoskeletal Questionnaire (NMQ) suggests that majority of those engaging in this livelihood experience MSDCs in the hands/wrists, lower back, and shoulders. Aims: Develop a model of causation of MSDC taking into consideration tasks, tools and workplace related factors which contribute to pet groomers MSDC in relation to wrists/hands, lower back and shoulders. Determine factors of pet grooming (tools, workplace, tasks) which significantly contribute to likelihood of experiencing MSDC by pet groomers in the wrists/hands, lower back and shoulders through logistic regression. Analyze the results of logistic regression models developed to assess predictability and generalizability between factors to the likelihood of experiencing MSDC. Methodology: Through research, observation and interview of pet groomers, a causation model was generated in order to determine factors that may affect MSDC experienced. Task analysis was conducted in order to assess the different tasks involved in pet grooming. Data gathering was conducted to determine tools existing utilized, task ix related factors, dog factors, etc. which was employed to develop the three logistic regression models addressing shoulder, lower back and hands/wrists MSDC. Logistic regression analysis was utilized in this study to determine significant factors that may contribute to MSDC experienced by pet groomers in the hands/wrists, shoulders and lower back. Results: Logistic regression model depicted several variables that significantly contribute to MSDC experience by pet groomers. Results indicate that the following variables namely, (1) number of dogs groomed, (2) percentage of ill tempered dogs, (3) percentage of long hair dogs groomed, (4,5) back twisted during blow drying and cutting, as well as (6) deviation from sink bottom to reach significantly contribute to MSDC in the lower back. On the other hand, variables that are found to significantly contribute to shoulders MSDC include (1) arms lifted during blow drying task, (2) percentage of large breed dogs, (3) percentage of ill-tempered dogs. Last, factors that contribute to MSDC of the hands/wrists include (1) number of dogs groomed, (2) percentage of long hair dogs, (3) percentage of ill-tempered dogs, (4,5) repetitive movement in grooming, and blowdrying, (5) type of scissor grip and (6) type of finger handle. All models were assessed via goodness of fit tests and were found to have adequate fit. A statistical interpretation was given of the model-developed estimates in terms of odd ratio concept and estimated coefficients. Model validation was also conducted in order to assess discrimination power of the model and was found adequate. x Conclusion: A model of causation was generated and factors which can significantly contribute to MSDC were determined though logistic regression modeling, indicating that logistic regression is a promising tool in providing meaningful interpretations with regards to MSDC. Furthermore, logistic regression model also allows for the prediction of MSDC allowing one to assess and discriminate accordingly.